2006
DOI: 10.1152/ajprenal.00231.2005
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine2Areceptor vasodilation of rat preglomerular microvessels is mediated by EETs that activate the cAMP/PKA pathway

Abstract: Dilation of rat preglomerular microvessels (PGMV) by activation of adenosine A2A receptors (A2AR) is coupled to epoxyeicosatrienoic acid (EET) release. We have investigated the commonality of this signal transduction pathway, i.e., sequential inhibition of G(salpha), adenylyl cyclase, PKA, and Ca2+-activated K+ (KCa) channel activity, to the vasoactive responses to A2AR activation by a selective A2A agonist, CGS-21680, compared with those of 11,12-EET. Male Sprague-Dawley rats were anesthetized, and microdisse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
65
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 40 publications
13
65
0
Order By: Relevance
“…A1 receptor activation also seems to induce vasoconstriction through inhibitory G protein-dependant activation of phospholipase C. [32][33][34] A2 receptors produce vasodilation by stimulating adenylate cyclase activity to increase cAMP generation by coupling to stimulatory G proteins and also by activating vasodilation products of arachidonic acid. 18,35 Our results demonstrate that A1 receptors are more sensitive to adenosine than A2 receptors. At the low concentrations, adenosine predominantly activates A1 receptors leading to vasoconstriction, but at the high concentration, adenosine mainly activates the A2 receptors, resulting in marked vasodilation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A1 receptor activation also seems to induce vasoconstriction through inhibitory G protein-dependant activation of phospholipase C. [32][33][34] A2 receptors produce vasodilation by stimulating adenylate cyclase activity to increase cAMP generation by coupling to stimulatory G proteins and also by activating vasodilation products of arachidonic acid. 18,35 Our results demonstrate that A1 receptors are more sensitive to adenosine than A2 receptors. At the low concentrations, adenosine predominantly activates A1 receptors leading to vasoconstriction, but at the high concentration, adenosine mainly activates the A2 receptors, resulting in marked vasodilation.…”
Section: Discussionmentioning
confidence: 65%
“…17 A2 receptor-mediated vasodilation results from stimulation of Gs␣ leading to increased cAMP that is partially mediated via epoxyeicosatrienoic acid release. 18 Cytochrome P450 epoxygenase metabolites have been shown to alter vascular tone in afferent arterioles and modify the autoregulatory efficiency of the preglomerular microcirculation. 19 Adenosine has been suggested as both a mediator and a modulator of renal autoregulation.…”
mentioning
confidence: 99%
“…During the early differentiation of preadipocytes, inhibition of ERK and activation of the AMP-activated protein kinase (AMPK) and cAMP/protein kinase A (PKA) signaling pathways inhibit PPAR ␥ , C/EBP ␣ , and SREBP1c activation and adipocyte differentiation (39)(40)(41). Previous studies have demonstrated that promoting the effects of EETs attenuates ERK1/2 dephosphorylation in endothelial cells, activates AMPK activity in liver, and activates the cAMP/PKA pathway in the vascular system ( 12,42,43 ), suggesting that a complex interaction between CYP-derived EETs and multiple signaling pathways also likely exist in the early phase of adipogenesis. Future studies are needed to delineate the key signaling pathways that underlie the inhibitory effects of EETs on adipocyte differentiation.…”
Section: Downloaded Frommentioning
confidence: 99%
“…This paracrine mechanism involves the Ga s protein, adenylyl cyclase activation, and an increase in cAMP (5). A similar pathway involving ADP-ribosylation of Ga s , an increase in cAMP, and protein kinase A activation produces EET-stimulated vasodilation of preglomerular renal microvessels (24). Likewise, a cAMP-protein kinase A mechanism mediates the EET-stimulated increase in StAR protein and steroid hormone production (25).…”
Section: Eet-activated Signaling Pathwaysmentioning
confidence: 99%